Factors Influencing Nutrition Status in Toddlers in Work Areasuptdcommunity Health Center Karang Tumaritis Nabire District - Deborah Deba; Nur Susan Iriyanti Ibrahim; Gandhi Pratama (Sekolah Tinggi Ilmu Kesehatan Kesdam IV, Diponegoro Semarang, Indonesia, 2024)
Background: Malnutrition including undernutrition is a major health problem for toddlers. Data from the Nabire District Health Office shows the number of cases of toddlers experiencing undernutrition.in Nabire Regency is 177 toddlers in 2023. Data from the UPTD Karang Tumaritis Health Center shows that toddlers who experience malnutrition in the Working Area of ??the UPTD Karang Tumaritis Health Center, Nabire Regency in 2023 are 26 toddlers. Objective: The purpose of this study was to determine the factors that influence Malnutrition Status in Toddlers in Nabire. Method: The research design used was case control with purposive random sampling technique. The study population wasall toddlers in the Working Area of ??UPTD Karang Tumaritis Health Center, Nabire Regency. The sample used was 110 toddlers. While the respondents were mothers of toddlers. Sampling was carried out by accidental sampling from 208 toddlers. Data collection was carried out in the monthMarch to May 2024 includes dataprimary and secondary.Results: Data processing was carried out using a computer with the SPSS (Program for Social Scene) version 16.1 application with the chi-square test. The results of statistical analysis showed that the factors that influence malnutrition are infectious diseases (large p-value = 0.00), immunization status (p-value = 0.00), history of exclusive breastfeeding (p-value = 0.00), and unrelated factors, namely the level of maternal education (p-value = 0.25). Conclusion: Factors that influence malnutrition are infectious diseases, immunization status, history of exclusive breastfeeding. Suggestion: Early detection and prevention of malnutrition in children must be improved in the child growth and development monitoring program.